Only Little Justification for Regulation in the Postal Sector - Sven Heitzler (Weekly Report, 2008)
European postal markets are to be completely liberalized by the end of 2012 at the latest. At the same time national regulatory frameworks are being adapted to the new requirements. The extent to which the present monopoly suppliers will in future (continue to) be obliged to grant their competitors access to their network is also under discussion. In this respect the postal sector is often compared to the telecoms sector. However, the differences between the two industries are so great that regulation of telecommunications cannot be transferred to the mail sector. Obligations to provide network access and regulations on final prices in particular can scarcely be justified in the mail sector. The regulatory strategy that should therefore be pursued during the liberalization process is one that places the minimal requirements necessary to create the best possible conditions for effective competition, for example access to address lists and PO boxes.
Keywords: L51; L13; D43; 330; Postal economics; Postal regulation; Telecommunications regulation; Transferability